От Хиросимы до Фукусимы: [появится ли в России своя "Фукусима"?] / В. В. Сливяк - Сливяк Владимир Владимирович (Политика XXI века, 2012)
Экземпляры: СФ-11 (20120827) / Инвентарный номер: 41037z11 / Цена: 232.27 / Сис.шифр: 66.2(2) / Авт.знак: С 47 / ГРНТИ: 11 / ББК: 66.2(2Рос)